Hopping peak height algorithm for a one legged robot hopping height control - Azahar, Arman Hadi; Chong, Shin Horng; Mohamed Kassim, Anuar (2015)
This paper presents the hopping peak height algorithm in controlling the hopping height of a one legged hopping robot. The hopping mechanism produces continuous and rhythmic pattern. The continuous and rhythmic pattern behaviors produce oscillation feedback to the closed loop system and continuously produce oscillation error to the controller. Therefore, hopping peak height algorithm is designed and embedded into the closed loop control system feedback to determine the hopping peak of each produced hopping as a feedback. The existence of the hopping peak height algorithm assists the PI-CPG controller to converge the hopping height error approximately to zero.